Graphene-modified electrodes for sensing doxorubicin hydrochloride in human plasma - Chekin, Fereshteh; Myshin, Vladyslav; Ye, Ran; Melinte, Sorin; Singh, Santosh K.; Kurungot, Sreekumar; Boukherroub, Rabah; Szunerits, Sabine (Analytical and Bioanalytical Chemistry, 2019)
Doxorubicin (DOX), an anthracycline molecule, is currently one of the most widely used anticancer drugs in clinics. Systematic treatment of patients with DOX is known to be accompanied by several unpleasant side effects due to the toxicity of the drug. Thus, monitoring of DOX concentration in serum samples has become increasingly important to avoid side effects and ensure therapeutic efficiency. In this study, we discuss the construction of a disposable electrochemical sensor for the direct monitoring of DOX in clinical blood samples. The sensor is based on coating a gold electrode in a flexible integrated electrode construct formed on polyimide sheets using photolithography, with nitrogen-doped reduced graphene oxide (N-rGO) suspended in chitosan. Under optimized conditions, a linear relationship between the oxidative peak current and the concentration of DOX in the range of 0.010-15M with a detection limit of 10nM could be achieved. The sensor was adapted to monitor DOX in serum samples of patients under anticancer treatment.
Keywords: Disposable electrodes; doxorubicin; Nitrogen-doped reduced graphene oxide; Serum